Pemberdayaan Pelaku Ekonomi Sektor Melalui Peningkatan Pemahaman Konsep Wisata Syariah - Ansharullah Ansharullah; Harum Natasha; Adam Malik Indra (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2018)
The purpose of this dedication is to improve the understanding of the concept of sharia tourism for economic actors in the tourism sector, to improve services and to increase the income for economic actors in the tourism sector in Rokan Hulu regency, Riau province. The subject of this dedication is the economic actors in the tourism sector in the Great Islamic Center mosque in Rokan Hulu district. While the object is to increase the understanding of Islamic tourism. Empowerment methods are Participatory Learning and Action (PLA) Models, or Participatory Learning and Practical Processes by holding beginning and Final Competency Tests. Based on the results of dedication, it can be concluded that the knowledge and understanding of economic actors in the tourism sector at the Islamic Grand Mosque of Rokan Hulu district about the concept of sharia tourism is increased.